Análise termodinâmica dos complexos convectivos de mesoescala atuantes na costa leste do nordeste brasileiro - Silveira, Marcio Henrique dos Santos (2012)
Thermodynamic characteristics analysis of 80 MCC events during 10 years (1999-2009) in the Brazilian Northeast was the principal goal of this study. CCM events were observed more frequently (66%) in the dry season (January March). Reanalysis data showed SST temperatures above 27°C in adjacent ocean, and a 180° wind variation in relation to lower and higher levels. MCC development (declining) stage was associated more frequently with upslope (downslope) trajectory. K ant TT indexes showed more instability of the upslope air parcels in the majority of the events. In development stage, Convective Inhibition (CIN) values showed a decrease in its values and in the declining stage an increase were seen. Radiosonde data presented average values in consistency with reference data. Potential Instability showed influence in most of the cases, especially in the upslope events in the development stage. The influence of dynamical aspects on the instability took place in a better way for the MCC than the convective forcing